Union And Employer Collaboration On Company Productivity X - Eka Saputra; Guruh Novan Aldianto; Aisyah Zahra Maghfirah (Publikasi Indonesia, 2023)
Beginning in 2020–2022 during the COVID-19 epidemic, a company experienced a lot of productivity decline, employers need to think about how productivity is maintained and increased from various existing conditions. In 2023 the COVID-19 pandemic became an endemic, and the economy began to grow from various sectors, the research aims to describe clearly and completely the collaboration of trade unions and employers on company productivity through the fulfillment of welfare for workers that have an impact on company productivity in the pandemic of Covid-19. Descriptive qualitative data collecting is the research methodology used through unstructured interviews, field research, and literature study for data analysis techniques using data reduction techniques that focus on the relationship between collaboration and productivity. The results of this research conducted at PT X, which is engaged in the electronics business for the defense and infrastructure industries, the first problem shows that trade unions take a role to encourage companies not to reduce the welfare facilities that have been provided and improve existing welfare facilities during the Covid-19 pandemic. The second problem, based on the report data from 2020 to 2022, the fulfillment and improvement of welfare is well proven and has an effect on increasing productivity for the company, besides that the pattern of harmonious industrial relations and conducive working conditions can make communication between trade unions and employers well as prevent disputes and be a factor in increasing productivity in company X. Result in this research is that companies should maintain the fulfillment of welfare and maintain the collaboration that has been implemented so that worker productivity continues to grow positively.